2005
DOI: 10.1007/s10551-004-5969-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Commitment and Ethical Consumer Behavior in a Retail Setting: The Case of Receiving Too Much Change at the Checkout

Abstract: In this study, we conducted two experiments to examine the effect of relationship commitment on the reaction of shoppers to receiving too much change, controlling for the amount of excess change. Hypotheses based on equity theory, opportunism and guilt were set up and tested. The first study showed that, when the less committed consumer is confronted with a large excess of change, he/she is less likely to report this mistake, compared with a small excess. Conversely, consumers with a high commitment towards th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 65 publications
1
35
0
3
Order By: Relevance
“…By doing so, the present research gives empirical support to earlier made suggestions (e.g. Baumeister et al, 1994;Marks and Mayo, 1991;Steenhaut and Van Kenhove, 2005;Strutton et al, 1994;Tangney and Dearing, 2002) and confirms Vitell's (2003) pressing statement that factors other than ethical beliefs influence ethical behavioral intentions. More specifically, we established the anticipation of guilt feelings as a partial mediator between a consumer's ethical beliefs (anteceded by idealism) and ethical intentions.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…By doing so, the present research gives empirical support to earlier made suggestions (e.g. Baumeister et al, 1994;Marks and Mayo, 1991;Steenhaut and Van Kenhove, 2005;Strutton et al, 1994;Tangney and Dearing, 2002) and confirms Vitell's (2003) pressing statement that factors other than ethical beliefs influence ethical behavioral intentions. More specifically, we established the anticipation of guilt feelings as a partial mediator between a consumer's ethical beliefs (anteceded by idealism) and ethical intentions.…”
Section: Discussionsupporting
confidence: 88%
“…Following the suggestions made previously about the potential positive impact of guilt in consumer ethics (e.g. Baumeister et al, 1994;Marks and Mayo, 1991;Steenhaut and Van Kenhove, 2005;Strutton et al, 1994;Tangney and Dearing, 2002) and in line with recent theoretical and empirical research supporting anticipated emotions as predictors of intentions to act (e.g. Parker et al 1995;Richard et al, 1996;Zeelenberg and Beattie, 1997), we hypothesize consumers' ethical intentions to be positively influenced by anticipated guilt.…”
Section: Research Modelmentioning
confidence: 54%
See 2 more Smart Citations
“…Neutralisation, false-returning purchased items as "faulty" or "unwanted" (associated with thrill-seeking and less self-consciousness), anticipated guilt following unethical consumer activity, and the influence of guilt and opportunism on receiving too much change at a supermarket checkout have all been examined (De Bock & Van Kenhove, 2011;Harris, 2008;Steenhaut & Van Kenhove, 2006;Steenhaut & Van Kenhove, 2005). Moore et al's (2012) systematic studies into moral disengagement in occupational settings measured Machiavellianism alongside measures of empathy and perspective-taking, finding these predictors associated with a greater ability to morally disengage, their effect was replicated across two studies, while a fourth study found Moral disengagement and the Dark Triad: 4 dispositional guilt negatively correlated with the propensity to morally disengage.…”
mentioning
confidence: 99%